THE ROLE OF ENDOTHELIAL DYSFUNCTION IN THE DEVELOPMENT OF OSTEOARTHRITIS IN WOMEN DURING MENOPACTERIC PERIOD - Dilnoza Sagatova (Modern American Journals, 2025)
Osteoarthritis is a pathological lesion of the joints, characterized by structural changes in the articular cartilage and subchondral bone, as well as overt or covert moderate synovitis. Osteoarthritis is a pressing medical and social problem for most countries in the world due to its high prevalence, which reaches about 25% of the population. This disease is most common among women and is one of the reasons for decreased ability to work and increased disability. In osteoarthritis, endothelial dysfunction is a component of microcirculatory disorders. Desquamated endothelial cells and vascular endothelial growth factor are the main indicators of damage to the microcirculatory bed. Under the influence of proinflammatory cytokines, homeostasis in the microcirculatory link is destabilized. A necessary element in diagnosing osteoarthritis is the detection of an early marker.
Keywords: Osteoarthritis, microcirculatory imbalance, nitric oxide, monocyte chemoattractant protein.